A Development and Validation of RP-HPLC Method for the Determination of Degradation Impurities in Anagrelide Dosage Form. Issue 5 (3rd September 2021) - Mallavarapu, Ravindra; Pavithra, Kommera; Katari, Naresh Kumar; Dongala, Thirupathi
Abstract: A simple and selective method for liquid chromatography has been developed to determine the degradation impurities in solid oral dosage forms of Anagrelide (Antithrombocythemic agent). An excellent resolution between Anagrelide (ANG) and its related substances was achieved with Symmetry C8, 250 mm × 4.6 mm, 3.0 μm column. and mobile phase A (phosphate buffer, pH 4.1) and mobile phase B (the mixture of acetonitrile, methanol, and buffer in the ratio of 40:40:20 v/v/v). The column oven temperature was maintained at 40°C. The flow rate was fixed at 0.8 mL/min, and elution was monitored at 254 nm using a UV detector. The method was validated for precision, accuracy, specificity, linearity, and sensitivity. The validation studies demonstrated that the current HPLC method is reproducible, specific and accurate for its intended purpose. Linearity was observed for ANG, and its impurities are more than (R 2 > 0.995). The limit of detection and limit of quantitation (LOQ) was found to be adequate (< 0.05 %) for the estimation of impurities. The RSD for intra- day and inter-day precision was found to be between 0.5 % to 2.5 %. The percentage of recovery was found between 95 % to 105 %. Forced degradation studies were performed on ANG under different conditions such as acidic, basic, oxidation, photostability, and thermal degradation. Based on the results, this is found to be simple, specific, precise, accurate, linear, and stability-indicating method. Hence it can be used to determine the Anagrelide-related impurities in the capsule dosage form. It is economically feasible and user-friendly method. The proposed method was successfully applied in quality control labs for stability analysis. GRAPHICAL ABSTRACT: UF0001